2016
DOI: 10.1667/rr14331.1
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of Radiation Sensitivity in Nasopharyngeal Carcinoma Cells via Activation of the Rac1/NADPH Signaling Pathway

Abstract: We reported in an earlier study that using mass spectrometry and bioinformatic analysis demonstrated Rac1 protein might be mostly mitochondrial target in the radiosensitization process of nasopharyngeal carcinoma CNE-1 cells. The goal of our current study was to reveal the relationship between Rac1/NADPH pathway and radiosensitization in CNE-1 cells using Rac1 activator, phorbol 12-myristate 13-acetate (PMA) and Rac1 inhibitor NSC23766. The Rac1-GTP expression was determined using a pulldown assay, the Rac1 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…PMA can activate the NADPH oxidase activity and NSC23766 inhibits its activity. No significant cytotoxicity to SKOV3-PM4 cells was found when the concentration of PMA and NSC23766 was 100 nM and 12.5 µM, respectively (21). Considering that the inhibitory rate of SKOV3-PM4 cells treated with rhein alone was <20%, the concentration of rhein was chosen as ≤11.3 µM.…”
Section: Methodsmentioning
confidence: 99%
“…PMA can activate the NADPH oxidase activity and NSC23766 inhibits its activity. No significant cytotoxicity to SKOV3-PM4 cells was found when the concentration of PMA and NSC23766 was 100 nM and 12.5 µM, respectively (21). Considering that the inhibitory rate of SKOV3-PM4 cells treated with rhein alone was <20%, the concentration of rhein was chosen as ≤11.3 µM.…”
Section: Methodsmentioning
confidence: 99%
“…28 It has been observed that Nox4 expression continues to increase at all time points from 1 day to 6 months post X-ray radiation in mice lung tissue. 29 Similarly, low-dose γ irradiation is capable of upregulating NADPH oxidase in central nervous system in mice.…”
Section: Discussionmentioning
confidence: 95%
“…Besides heavy ion radiation, X-ray radiation could also significantly activate NADPH oxidase and enhance the production of ROS, leading to X-radiation-induced growth inhibition of nasopharyngeal carcinoma cells. 28 It has been observed that Nox4 expression continues to increase at all time points from 1 day to 6 months post X-ray radiation in mice lung tissue. 29 Similarly, low-dose g irradiation is capable of upregulating NADPH oxidase in central nervous system in mice.…”
Section: Discussionmentioning
confidence: 95%
“…Rac1 and its effectors can activate mitogenic pathways, including the MAPK cascades, leading to changes in cell cycle progression (Olson et al, 1995;Yang et al, 2008). Rac1 has been consistently involved in the activation of pro-survival pathways in cancer cells, such as NF-κB, thereby counterbalancing the apoptotic responses triggered by chemotherapeutic agents and radiation therapy (Friedland et al, 2007;Han et al, 2013;Wang et al, 2013Wang et al, , 2016Hein et al, 2016). Regarding cellular metabolism, Rac1 has been widely associated with macropinocytosis, a mechanism of endocytic uptake of extracellular fluid that assists in meeting the increased demand of nutrients required for cancer cells to proliferation (Erami et al, 2017;Ramirez et al, 2019).…”
Section: Location Is the Key: Why Do Cancer Cells Need Multiple Rac-gmentioning
confidence: 99%